Zircon U‐Pb Dating of a Lower Crustal Shear Zone: A Case Study From the Northern Sector of the Ivrea‐Verbano Zone (Val Cannobina, Italy). Issue 1 (31st January 2018) - Langone, A.; Zanetti, A.; Daczko, N. R.; Piazolo, S.; Tiepolo, M.; Mazzucchelli, M.
Abstract: A geochronological study was performed on zircon grains from a middle‐lower crustal shear zone exposed in the northern sector of the Ivrea‐Verbano Zone (Southern Alps, Italy) for the first time. The shear zone developed at the boundary between mafic rocks of the External Gabbro unit and ultramafic rocks of the Amphibole Peridotite unit. It is ~10–20 m wide, can be followed along a NE strike for several kilometers, and consists of an anastomosing network of mylonites and ultramylonites. Zircon grains were studied in thin sections and as separates from three representative outcrops along the shear zone. Zircon grains are more abundant in the shear zone compared to wall rocks and are generally equant, rounded to subrounded with dimensions up to 500 μm. U‐Pb data are mainly discordant, and the apparent 206 Pb/ 238 U dates show a large variation from Permian to Jurassic. Isotopic data, combined with microstructural, morphological, and internal features of zircon, reveal an inherited age component and suggest partial zircon recrystallization under high‐temperature conditions during Late Triassic to Early Jurassic. High‐temperature deformation in the shear zone, at lower crustal levels, was coeval with amphibolite to greenschist facies mylonitic deformation at upper crustal levels and is inferred to be related to Mesozoic rifting processes at the Adriatic margin. Key Points: Lower crustal high‐temperature deformation is Late Triassic to Early Jurassic Large‐scale shear zones at different crustal levels were coeval Zircon U‐Pb dating of mylonitic mafic rocks provides the first evidence of lower crustal deformation associated with Mesozoic rifting